Relationship between social support and recreation physical activity among workers - Duarte, Táila Raquiélli Amaro (2014)
The success of interventional strategies aimed at promoting physical activity passes by the understanding of the determinant factors of this behavior. Thus, the aim of this study was to investigate possible associations between social support and the practice of recreational physical activity among adults. This is a cross-sectional study conducted with 227 adults (152 men) aged between 18 and 65 years, selected from a company located in the city of Londrina / PR. Information on leisure-time physical activity were obtained using the International Physical Activity Questionnaire (long version). Subjects who reported a minimum amount of 150 minutes per week on walks (WAL) or moderate to vigorous physical activities (MVPA) were considered active. Social support was determined using the Social Support Scale for Physical Activities. Crude and adjusted Poisson regression analyses (gender, age, marital status and educational level) were used to test associations between social support received from family or friends and WAL and MVPA. Most subjects reported never having received social support from family and friends to practice WAL and MVPA. Crude and adjusted analyses revealed that social support was significantly and positively associated with MVPA (P < 0.01). The probability of being active in leisure time was 75 % higher in subjects who received social support from friends (RP = 1.75, CI 95% = 1.09 - 2.81) and 124 % higher among those who received social support in combination (family and friends) (RP = 2.24, CI 95% = 1.55 - 3.25). Social support was not associated with the practice of WAL (P = 0.75). In conclusion, social support seems to be correlated with the practice of MVPA. The support from family and friends can be an important tool for promoting physical activity in adults.